Increased Risk of Pyogenic Liver Abscess Among Patients With Colonic Diverticular Diseases: A Nationwide Cohort Study. Issue 49 (December 2015) - Tsai, Ming-Shian; Lee, Hui-Ming; Hsin, Ming-Che; Lin, Cheng-Li; Hsu, Chung-Y.; Liu, Yen-Tze; Kao, Chia-Hung
Abstract : Abstract: Whether patients with diverticular diseases exhibit a higher risk of developing pyogenic liver abscess (PLA) remains inconclusive. From the inpatient claims in Taiwan's National Health Insurance Research Database, we identified 54, 147 patients diagnosed with diverticulosis in the 1998 to 2010 period and 216, 588 controls without the disorder. The 2 cohorts were matched by age, sex, and admission year, and were followed up until the end of 2010 to estimate the risk of PLA. Overall, the incidence of PLA was 2.44-fold higher in the diverticular-disease group than in the controls (11.5 vs 4.65 per 10, 000 person-year). The adjusted hazard ratio (aHR) of PLA was 2.11 (95% confidence interval [CI], 1.81–2.44) for the diverticular-disease group, according to a multivariate Cox proportional hazards regression model. The age-specific data showed that the aHR for the diverticular-disease group, compared with the controls, was the highest inpatients younger than 50 years old (aHR, 4.03; 95% CI, 2.77–5.85). Further analysis showed that the diverticular-disease group exhibited an elevated risk of PLA regardless of whether patients had diverticulitis. The patients with diverticular diseases exhibited a higher risk of PLA.